AN ANALYSIS OF THE COHESION OF THE STUDENTS’ DESCRIPTIVE TEXT WRITING IN SMP NEGERI 01 TAYU IN THE ACADEMIC YEAR 2021/2022 - Nudya Anjanita Saputri Ansori; Suwandi Suwandi; Sri Wahyuni (Wawasan Pendidikan, 2023)
This final project studied the analysis of the cohesion found on the students’ descriptive test writing in SMP N 01 Tayu. The design of the research was descriptive qualitative research. The objectives of the study were (1) To find out the type analysis of cohesion competence by the eight grade SMP 01 Tayu in producing descriptive text, (2) To show the dominant in producing cohesion at their descriptive text at eight grade SMP 01 Tayu, (3) to describe the students’ cohesion competence in producing descriptive text. The object of the research were eight grade SMP N 1 Tayu. The instruments of the study were the data from the students descriptive text. This discussions from prior chapters are to be summarized to achieve the purpose of the study. The first one is the grammatical cohesion device, and the second one is the lexical cohesion devices. The grammatical cohesion device are the reference, substitution, ellipsis, and conjunction. Meanwhile, the lexical cohesion devices are the reiteration and the collocation. Then the are 5 types of the reiteration lexical devices. There were repetition, synonymy, hyponymy. Meronymy, and antonymy. And then, the last part is the collocation.